Overruns in Transport Infrastructure Projects: A View from the Inside Out - Love, Peter; Smith, J.; Simpson, I.; Regan, M.; Olatunji, Oluwole (Pion, 2014)
Cost and schedule overruns are endemic features of transport infrastructure projects. Despite the considerable amount of research within the field of transport and planning in the past 30 years, limited progress has been made to improving the performance of projects. We contend that this will continue to be an issue as long as research efforts focus on the ‘outside view’ with emphasis being placed upon strategic misrepresentation and optimism bias. Understanding ‘why’ and ‘how’ projects overrun, particularly from both outside’ and ‘inside’ perspectives, is pivotal to reducing their impact and occurrence. Thus, in conjunction with the transport and planning literature, reference to cost overrun studies undertaken within the field of construction and engineering are examined, particularly with reference to the points for determining the pre and post contract award stages as they are intimately connected. The objective of this paper is to provide policy makers, industry, voluntary organizations and the public at large with an ameliorated understanding about time and cost overrun phenomenon. Suggestions to mitigate overruns based upon recent process and technological innovations are identified and discussed.